PENGARUH NUMBERED HEAD TOGETHER BERBANTUAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN - Ervina, Ervina; Rosnita, Rosnita; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrsct This research is purpose to analyze how model cooperative type numbered head together with learning video influence the result of education citizenship at grade V Elementary School 33 Pontianak Utara. The method used is an experiment with quasi experimental design type  nonequivalent control group design. The population and sample of this research are  all students at grade V Elementary School 33 Pontianak Utara, consist of two classes with totaling 56 students. The result of analyze average posttest control class and experimental is 71,28 and 80,07. Obtained  tcount (4.484) and ttable (2,006), because of  tcount> ttable, so Ha was accepted. Based on calculation of effect size obtained Δ = 0.84, with the high criteria. In conclusion research is model cooperative type numbere head together with learning video give high impact on the result of education citizenship at grade V in Elementary School 33 Pontianak Utara.  Keywords: Numbered Head Together, Learning Outcomes